Analisis Tindak Tutur Ekspresif dalam Film Home Sweet Loan Karya Almira Bastari Kajian Pragmatik - Ibrahim, Tiara; Rahmi, Elvi; Indryani, Dian (JURNAL PERSPEKTIF PENDIDIKAN, 2025)
This study examines expressive speech acts in Almira Bastari's film "Home Sweet Loan" as a manifestation of the main character's psychological attitudes toward the situations they experience. The main focus of this study is to identify and analyze various types of expressive utterances that appear in dialogues between characters, such as expressions of gratitude, anger, disappointment, happiness, and regret. This study uses pragmatics with Searle's theory of expressive speech acts as its theoretical foundation. The research method used is descriptive qualitative, using direct dialogue recording from the film as the primary data. The analysis shows that expressive utterances in the film not only reflect the characters' emotions but also represent complex social relations and interpersonal dynamics. Thus, this film is an effective medium for observing the realization of pragmatics in everyday communication through expressive language.